Simple potting process for direct-drive motor stator based on rubber sleeve and supporting block
Patent Information
- Application Number
- CN202611057900.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-16
- Publication Date
- 2026-10-09
AI Technical Summary
1、由于本申请采用含有纳米四氧化三铁颗粒的磁响应硅胶胶套并对其表面进行防粘处理,与非铁磁性撑块过盈套合后能够实现与定子硅钢片内壁的柔性贴合,改善因内孔尺寸公差导致的刚性接触不良问题,由于复合灌封胶中包含第一膨胀微球和第二膨胀微球,在阶梯固化过程中两类微球先后触发膨胀,补偿灌封胶固化产生的体积收缩,有利于减少收缩对灌封层均匀性的影响,由于在预固化阶段施加旋转磁场,处理件中的磁响应硅胶胶套产生响应,且阶梯固化配合自然冷却后撑块胶套组合体可顺利脱模,因此,能够使灌封胶层更加均匀,减少绕组间隙中残留的气泡,从而改善灌封体的绝缘性能和散热效果。
Smart Images

Figure CN122890804A_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of motor manufacturing technology, and more specifically, it relates to a simplified potting process for the stator of a direct-drive motor based on a rubber sleeve and a support block. Background Technology
[0002] A direct-drive motor is a type of motor that drives the load directly by the rotor without the need for a reduction gear. The uniformity of the air gap between the stator and the rotor directly affects the motor's operating accuracy and torque stability. To ensure the heat dissipation efficiency, mechanical strength, and electrical insulation performance of the stator windings during operation, the stator windings are usually potted. This involves filling the space between the inner hole of the stator silicon steel sheet and the winding with potting compound, so that the windings and the silicon steel sheet are cured into one piece.
[0003] Currently, the common method for potting stators of direct drive motors is to directly insert rigid metal supports into the inner holes of the stator silicon steel sheets to form a potting cavity. However, the rigid fixture and the inner hole of the silicon steel sheet are in hard contact. Due to the dimensional tolerance of the inner hole after the silicon steel sheet is stamped, the two cannot achieve uniform fit, which easily leads to uneven thickness of the potting adhesive layer and air bubbles in the winding gap, affecting the insulation performance and heat dissipation effect of the potting body. Summary of the Invention
[0004] To address the problems of uneven potting layer thickness and residual air bubbles in the winding gaps in existing simple potting processes for direct-drive motor stators, which affect the insulation performance and heat dissipation of the potting compound, this application provides a simple potting process for direct-drive motor stators based on a rubber sleeve and a support block.
[0005] This application provides a simplified potting process for the stator of a direct-drive motor based on a rubber sleeve and a support block, employing the following technical solution: A simplified potting process for a direct-drive motor stator based on a rubber sleeve and a support block includes the following steps: S1. Prepare a magnetically responsive silicone sleeve and perform an anti-sticking treatment on the surface of the magnetically responsive silicone sleeve to obtain a treated sleeve. The magnetically responsive silicone sleeve contains nano-iron oxide particles. S2. The processed rubber sleeve is interference-fitted onto the outer circular step of the non-ferromagnetic support block to form a support block rubber sleeve assembly. S3. Prepare a composite potting compound, wherein the composite potting compound comprises epoxy resin, a first expanded microsphere, and a second expanded microsphere; S4. Insert the support block and rubber sleeve assembly into the inner hole of the silicon steel sheet of the direct drive motor stator to be potted, so that the end face of the support block fits against the end face of the stator to form a potting assembly. S5. Place the potting assembly in a vacuum environment and inject the composite potting compound into the cavity between the inner wall of the stator and the rubber sleeve to obtain the treated part. S6. The processed part is placed in a rotating magnetic field for step curing, the step curing includes a pre-curing stage and a post-curing stage, and a rotating magnetic field is applied in the pre-curing stage. S7. After the stepped solidified part has cooled naturally, remove the support block rubber sleeve assembly from the stator to complete the demolding.
[0006] By adopting the above technical solution, the use of a magnetically responsive silicone sleeve containing nano-ferric oxide particles and its surface treated with an anti-stick coating allows for flexible bonding with the inner wall of the stator silicon steel sheet after interference fitting with the non-ferromagnetic support block. This improves the problem of poor rigid contact caused by the tolerance of the inner hole size. Since the composite potting compound contains first and second expanding microspheres, the two types of microspheres are triggered to expand sequentially during the stepped curing process, compensating for the volume shrinkage caused by the curing of the potting compound. This helps to reduce the impact of shrinkage on the uniformity of the potting layer. Because a rotating magnetic field is applied during the pre-curing stage, the magnetically responsive silicone sleeve in the processed part responds. After stepped curing and natural cooling, the support block and sleeve assembly can be easily demolded. Therefore, the potting compound layer can be made more uniform, reducing the number of residual air bubbles in the winding gap, thereby improving the insulation performance and heat dissipation effect of the potting compound. This solves the problem that the existing simple potting process for direct drive motor stators easily leads to uneven potting compound layer thickness and residual air bubbles in the winding gap, affecting the insulation performance and heat dissipation effect of the potting compound.
[0007] Preferably, in step S1, obtaining the processed rubber sleeve includes the following steps: By weight, 95-105 parts of methyl vinyl silicone rubber raw rubber, 3-5 parts of nano iron oxide particles, 10-20 parts of fumed silica, and 1-1.5 parts of vulcanizing agent are mixed and molded to obtain a magnetically responsive silicone sleeve. The average particle size of the nano iron oxide particles is 30-50 nm. The outer surface of the magnetically responsive silicone sleeve is subjected to plasma activation treatment, spraying of a base layer sol and spraying of a surface layer of fluorosilane in sequence to form an anti-stick coating, thus obtaining the treated sleeve. The base layer sol is prepared by mixing silica sol and methyltriethoxysilane in a molar ratio of 1:1.1 to 1.3, and the surface layer of fluorosilane is an anhydrous ethanol solution of perfluorodecyltrimethoxysilane with a mass fraction of 1 to 2%.
[0008] By adopting the above technical solution, a magnetically responsive silicone sleeve containing nano-iron oxide particles is prepared by mixing and molding. Then, plasma activation, spraying of the bottom sol and the top fluorosilane to form an anti-stick coating are carried out in sequence. This makes the sleeve not only have magnetic field response capability but also low surface energy characteristics. When it is used in conjunction with the subsequent rotating magnetic field, it can produce controllable deformation. At the same time, it reduces the interfacial adhesion between the sleeve and the potting compound, which is conducive to smooth demolding after curing.
[0009] Preferably, in step S2, the non-ferromagnetic support block is made of 304 austenitic stainless steel or beryllium copper alloy, and 6 to 8 axial grooves are uniformly opened along the circumference on the outer circular step. Polyether ether ketone (PEEK) isolation strips are embedded in the grooves. The top surface of the PEEK isolation strips is 0.03 to 0.08 mm lower than the outer circular surface of the support block. The surface of the non-ferromagnetic support block is plated with a hard chromium layer with a thickness of 10 to 15 μm.
[0010] By adopting the above technical solution, using a non-ferromagnetic support block and embedding a polyetheretherketone (PEEK) isolation strip in an axial groove on the outer circular step, combined with hard chrome plating, the interference of the support block on the magnetic field can be avoided, ensuring the effective effect of the rotating magnetic field on the magnetic particles inside the rubber sleeve. At the same time, it reduces the long-term frictional loss between the rubber sleeve and the support block, which is conducive to the stable and repeated use of the support block and rubber sleeve assembly.
[0011] Preferably, in step S3, the preparation of the composite potting compound includes the following steps: By weight, 95-105 parts of epoxy resin, 1.2-1.8 parts of first expanded microspheres, 1.2-1.8 parts of second expanded microspheres, 8-12 parts of curing agent, 0.3-0.8 parts of accelerator and 3-7 parts of reactive diluent are mixed, stirred evenly and degassed to obtain composite potting compound.
[0012] By adopting the above technical solution, epoxy resin is mixed with first expanded microspheres, second expanded microspheres, curing agent, accelerator and reactive diluent to degas, and a composite potting compound containing dual-trigger temperature expanded microspheres is obtained. This adhesive can achieve staged volume compensation in the subsequent step curing process, which is beneficial to suppress curing shrinkage from the source and reduce winding displacement.
[0013] Preferably, the first expandable microsphere has an expansion initiation temperature of 72-78°C, an average particle size of 20-30 μm, and a maximum expansion ratio of 3-5 times; the second expandable microsphere has an expansion initiation temperature of 92-98°C, an average particle size of 25-35 μm, and a maximum expansion ratio of 3-4 times.
[0014] By adopting the above technical solution, the first expansion microsphere and the second expansion microsphere have a lower expansion initiation temperature and a higher expansion initiation temperature, respectively. When used together, they can trigger expansion successively in the pre-curing stage and the post-curing stage, jointly covering the complete temperature range of potting compound curing, which is beneficial to achieve volume shrinkage compensation throughout the process.
[0015] Preferably, the epoxy resin is a bisphenol A type epoxy resin with an epoxy equivalent of 180-200 g / eq, the curing agent is dicyandiamide, the accelerator is 2-methylimidazole, and the reactive diluent is butyl glycidyl ether.
[0016] By adopting the above technical solution, the curing system composed of bisphenol A epoxy resin, dicyandiamide, 2-methylimidazole and butyl glycidyl ether can be well compatible with the two types of expandable microspheres, ensuring that the expansion timing of the microspheres during the curing process matches the resin gelation process, which is conducive to the effective performance of the expansion compensation effect.
[0017] Preferably, in step S5, the absolute pressure of the vacuum environment is ≤50Pa, the rising speed of the composite potting compound liquid surface during injection is 5-12mm / s, and the vacuum is maintained for 1-3 minutes after injection.
[0018] By adopting the above technical solution, injecting composite potting compound into a vacuum environment under absolute pressure and maintaining vacuum can effectively remove gas from the stator winding gap, which helps to reduce bubble defects inside the potting compound after curing.
[0019] Preferably, in step S6, the pre-curing is performed by raising the temperature from room temperature to 73-77°C at a heating rate of 1-2°C / min and holding it at that temperature for 50-70 minutes. The post-curing is performed by raising the temperature to 115-125°C at a heating rate of 0.8-1.5°C / min and holding it at that temperature for 2-3 hours after the pre-curing is completed.
[0020] By adopting the above technical solution, pre-curing followed by post-curing can match the trigger temperature of the two types of expandable microspheres, which is conducive to the expansion of the microspheres in sequence within the preset temperature range, and realizes the phased compensation for curing shrinkage.
[0021] Preferably, in step S6, the rotating magnetic field is applied at the beginning of the pre-curing and heat preservation, with a magnetic field strength of 0.2 to 0.4T and a rotation speed of 60 to 120 rpm. The rotating magnetic field is turned off when the temperature rises to 100 to 105°C.
[0022] By adopting the above technical solution, the rotating magnetic field action window covers the main shrinkage stage of the potting compound and the temperature range in which the molecular chains of the sleeve still have the ability to move. This is beneficial to induce the magnetic particles in the sleeve to oriented and reduce the radial modulus of the sleeve, thereby actively releasing the shrinkage stress transmitted to the interface.
[0023] Preferably, in step S7, the cooling is performed by naturally cooling in the furnace to ≤40°C, then removing the product and allowing it to stand at room temperature until the surface temperature matches the ambient temperature. The total cooling time is 1.5 to 3 hours. The tensile force applied along the axial direction of the support block during demolding is 10 to 30 N. After demolding, the outer surface of the magnetically responsive silicone sleeve is wiped with a lint-free cloth dipped in anhydrous ethanol.
[0024] By adopting the above technical solution, natural cooling in the furnace can avoid thermal stress caused by rapid cooling, ensure that the rubber sleeve shrinks fully before demolding, and wipe the outer surface of the rubber sleeve with anhydrous ethanol after demolding to help keep the coating clean and extend the cycle of the assembly.
[0025] In summary, this application has the following beneficial effects: 1. Because this application uses a magnetically responsive silicone sleeve containing nano-ferric oxide particles and treats its surface with an anti-stick coating, it can achieve flexible contact with the inner wall of the stator silicon steel sheet after interference fitting with the non-ferromagnetic support block, thus improving the problem of poor rigid contact caused by the tolerance of the inner hole size. Since the composite potting compound contains a first expansion microsphere and a second expansion microsphere, the two types of microspheres are triggered to expand sequentially during the stepped curing process, which compensates for the volume shrinkage caused by the curing of the potting compound and helps to reduce the impact of shrinkage on the uniformity of the potting layer. Since a rotating magnetic field is applied in the pre-curing stage, the magnetically responsive silicone sleeve in the processed part responds, and the support block and sleeve assembly can be easily demolded after stepped curing and natural cooling. Therefore, the potting compound layer can be made more uniform, reducing the residual air bubbles in the winding gap, thereby improving the insulation performance and heat dissipation effect of the potting compound.
[0026] 2. This application adds first and second expansion microspheres with different expansion initiation temperatures to the composite potting compound. The two types of microspheres are triggered to expand sequentially during the stepped curing process, respectively compensating for the volume shrinkage generated in the pre-curing stage and the post-curing stage, thereby actively suppressing the curing shrinkage stress, effectively controlling the radial displacement of the stator winding, and ensuring the uniformity of the air gap between the rotor and the stator.
[0027] 3. This application induces the nano-iron oxide particles in the silicone sleeve to align in a direction by applying a rotating magnetic field during the pre-curing stage, thereby driving the molecular chain orientation of the sleeve and reducing the radial modulus of the sleeve. This allows the sleeve to actively release interfacial stress during the curing shrinkage process. At the same time, the anti-stick coating on the surface of the sleeve further reduces the interfacial adhesion force. The synergistic effect of these two factors significantly reduces the demolding force and extends the number of times the support block and sleeve assembly can be reused.
[0028] 4. This application utilizes vacuum injection and stepped curing to expel gas from the stator winding gaps and maintain a stable temperature field during curing. This ensures that the expansion timing of the microspheres matches the resin gelation process, resulting in a potting compound with extremely low bubble rate. This is beneficial for improving the electrical insulation reliability and long-term operational stability of the potting compound. Furthermore, assembly can be completed simply by interfering the treated adhesive sleeve with the support block and inserting it into the stator. After curing, natural cooling allows for self-demolding without the need for complex operations such as bolt tightening or hammering. This method is characterized by its ease of operation and high repeatability, making it compatible with the production rhythm of automated production lines and reducing manual intervention and equipment maintenance costs. Attached Figure Description
[0029] Figure 1 This is a flowchart of a simplified potting process for a direct-drive motor stator based on a rubber sleeve and a support block, as provided in this application. Figure 2 This is a schematic diagram of the encapsulation sleeve and its structure provided in this application. Detailed Implementation
[0030] The present application will be further described in detail below with reference to the accompanying drawings and embodiments.
[0031] Technical concept: During the stator potting process of a direct drive motor, when a rigid metal support block is directly inserted into the inner hole of the stator silicon steel sheet to form a potting cavity, due to the dimensional tolerance of the inner hole after the silicon steel sheet is stamped, the rigid support block cannot achieve uniform fit with the inner wall of the stator, which easily leads to uneven potting adhesive layer thickness and residual air bubbles in the winding gap. At the same time, the potting adhesive will inevitably shrink in volume during the curing process, and the resulting shrinkage stress will be transmitted to the stator winding, causing radial displacement of the winding and affecting the uniformity of the air gap between the rotor and the stator.
[0032] Based on the above findings, this application improves the uniformity of the potting compound thickness by adaptively compensating for the dimensional tolerance of the inner hole of the silicon steel sheet through the elastic deformation of the sleeve. At the same time, two types of expansion microspheres with different expansion initiation temperatures are introduced into the composite potting compound, which trigger expansion sequentially during the stepped curing process, actively compensating for the volume shrinkage caused by the curing of the potting compound and suppressing the winding displacement. In addition, a rotating magnetic field is applied during the pre-curing stage to induce the directional alignment of nano-iron oxide particles in the magnetic response sleeve, reducing the radial modulus of the sleeve and enabling it to actively release the interfacial stress during the curing shrinkage process. Combined with the anti-stick coating on the surface of the sleeve, low-resistance self-demolding is achieved.
[0033] Unless otherwise specified, all experimental methods used below are conventional methods. All materials, reagents, methods, and instruments used, unless otherwise specified, are conventional materials, reagents, methods, and instruments in this field, which can be obtained commercially or prepared according to literature methods by those skilled in the art.
[0034] Preparation Example 1: Preparation of the First Expanded Microsphere Preparation steps: Add 100g of acrylonitrile, 50g of methacrylic acid, 2.5g of benzoyl peroxide and 5g of sodium dodecyl sulfate to 500g of deionized water, and stir at 800rpm for 30 minutes at room temperature to form a uniform emulsion. The emulsion was transferred to a high-pressure reactor, and nitrogen gas was introduced to replace the air in the reactor three times. Then 30g of isobutane was added. The reactor was shut off, the temperature was raised to 75°C, and the polymerization reaction was carried out under autogenous pressure for 8 hours. After the reaction was completed, the reactor was cooled to room temperature to release unreacted isobutane gas. The reaction product was washed three times with deionized water, filtered, and dried in a vacuum drying oven at 50°C for 12 hours to obtain white powdery first expanded microspheres.
[0035] Preparation Example 2: Preparation of the Second Expanded Microspheres Preparation steps: Add 120g of acrylonitrile, 30g of methacrylic acid, 3g of benzoyl peroxide and 6g of sodium dodecyl sulfate to 600g of deionized water, and stir at 800rpm for 30 minutes at room temperature to form a uniform emulsion. The emulsion was transferred to a high-pressure reactor, and nitrogen gas was introduced to replace the air in the reactor three times. Then 35g of isobutane was added. The reactor was shut off, the temperature was raised to 95°C, and the polymerization reaction was carried out under autogenous pressure for 10 hours. After the reaction was completed, the reactor was cooled to room temperature to release unreacted isobutane gas. The reaction product was washed three times with deionized water, filtered, and dried in a vacuum drying oven at 50°C for 12 hours to obtain a white powdery second expanded microsphere.
[0036] Preparation Example 3: Preparation of the bottom sol Preparation steps: Take 100g of silica sol with a solid content of 30% and a particle size of 10~20nm, of which SiO2 content is 30g (0.5mol), and take 0.6mol of methyltriethoxysilane. The mass of the methyltriethoxysilane is 0.6mol × 178.3g / mol = 107.0g. 107g of methyltriethoxysilane was slowly added to 100g of silica sol at room temperature while stirring at 300rpm. After the addition was complete, stirring was continued for 3 hours to obtain a clear and transparent bottom sol.
[0037] Preparation Example 4: Preparation of Surface Fluorosilane Solution Preparation steps: Add 985g of anhydrous ethanol to a dry and clean glass container, and slowly add 15g of perfluorodecyltrimethoxysilane while stirring. Continue stirring for 15 minutes until completely dissolved to obtain a surface fluorosilane solution with a mass fraction of 1.5%. The prepared solution should be sealed and stored in a dry environment and used within 24 hours.
[0038] Preparation Example 5: Preparation of Processed Rubber Sleeves Preparation steps: Add 100g of methyl vinyl silicone rubber raw rubber, 4g of nano iron oxide particles, 15g of fumed silica, and 1.25g of vulcanizing agent bis2,5 to a two-roll mill and mix for 20 minutes at a roll temperature of 50℃ until the filler is evenly dispersed to obtain the compound. The compounded rubber was filled into a cylindrical rubber sleeve mold and vulcanized for 12 minutes under a pressure of 12MPa and a temperature of 170℃ using a flat vulcanizing machine. After vulcanization, the rubber was naturally cooled to room temperature in the mold and then demolded to obtain a magnetically responsive silicone rubber sleeve. The magnetically responsive silicone sleeve was placed in the vacuum plasma processing chamber, and a mixture of oxygen and argon in a volume ratio of 1:10 was introduced. The chamber pressure was 50 Pa, the radio frequency power supply was turned on, the power was 100 W, and the processing time was 90 seconds to complete the activation process. The base layer sol was uniformly sprayed onto the outer surface of the activated adhesive sleeve using an air spraying method, with a spray thickness of 10μm, and then pre-cured in an oven at 80℃ for 30 minutes.
[0039] After the base coat of adhesive is applied, the sleeve is immersed in the surface fluorosilane solution and left to stand at room temperature for 8 minutes to allow the solvent to evaporate. Then, it is cured in an oven at 120°C for 60 minutes to form an anti-stick coating, thus obtaining the treated sleeve.
[0040] Preparation Example 6: Formulation of Composite Potting Compound Preparation steps: Place 100g of bisphenol A type epoxy resin in a stainless steel container, heat it in a water bath to 50℃, and stir for 8 minutes at a constant temperature; 1.5g of the first expanded microsphere and 1.5g of the second expanded microsphere were slowly added to the preheated epoxy resin and stirred at 200 rpm for 10 minutes. Add 5g of butyl glycidyl ether, 10g of dicyandiamide, and 0.55g of 2-methylimidazole in sequence, and continue stirring at 120rpm for 8 minutes until all components are mixed evenly; Transfer the mixed adhesive to a vacuum degassing tank. The temperature of the degassing tank is controlled at 30°C. Vacuum is drawn to reduce the absolute pressure to 100Pa. Maintain this for 20 minutes until no visible bubbles escape from the liquid surface. The resulting composite potting compound should be used within 30 minutes.
[0041] To better understand the above technical solutions, the technical solutions of the present invention will be clearly and completely described below in conjunction with embodiments.
[0042] Please see the appendix Figure 1 Appendix Figure 2 The following is a further description with reference to the embodiments: Example 1: A simplified potting process for a direct-drive motor stator based on a rubber sleeve and a support block, comprising the following steps: S1. Prepare a magnetically responsive silicone sleeve and perform an anti-sticking treatment on the surface of the magnetically responsive silicone sleeve to obtain a treated sleeve. The magnetically responsive silicone sleeve contains nano-iron oxide particles. The process of obtaining the processed rubber sleeve includes the following steps: By weight, 100 parts of methyl vinyl silicone rubber raw rubber, 4 parts of nano iron oxide particles, 15 parts of fumed silica and 1.25 parts of vulcanizing agent are mixed and molded to obtain magnetically responsive silicone sleeves. The average particle size of the nano iron oxide particles is 40 nm. The outer surface of the magnetically responsive silicone sleeve is subjected to plasma activation treatment, spraying of the bottom layer sol and spraying of the top layer fluorosilane in sequence to form an anti-stick coating, thus obtaining the treated sleeve. The bottom layer sol is prepared by mixing silica sol and methyltriethoxysilane in a molar ratio of 1:1.2, and the top layer fluorosilane is an anhydrous ethanol solution of perfluorodecyltrimethoxysilane with a mass fraction of 1.5%.
[0043] S2. The processed rubber sleeve is interference-fitted onto the outer circular step of the non-ferromagnetic support block to form a support block rubber sleeve assembly. The non-ferromagnetic support block is made of 304 austenitic stainless steel or beryllium copper alloy. Seven axial grooves are evenly opened along the circumference on the outer circular step. Polyether ether ketone (PEEK) isolation strips are embedded in the grooves. The top surface of the PEEK isolation strips is 0.055 mm lower than the outer circular surface of the support block. The surface of the non-ferromagnetic support block is plated with a hard chromium layer with a thickness of 12.5 μm.
[0044] S3. Prepare a composite potting compound, which includes epoxy resin, first expanded microspheres, and second expanded microspheres. The preparation of the composite potting compound includes the following steps: By weight, 100 parts of epoxy resin, 1.5 parts of first expanded microspheres, 1.5 parts of second expanded microspheres, 10 parts of curing agent, 0.55 parts of accelerator and 5 parts of reactive diluent are mixed, stirred evenly and degassed to obtain composite potting compound.
[0045] The first expanding microsphere has an expansion initiation temperature of 75℃, an average particle size of 25μm, and a maximum expansion ratio of 4 times. The second expanding microsphere has an expansion initiation temperature of 95℃, an average particle size of 30μm, and a maximum expansion ratio of 3.5 times.
[0046] The epoxy resin is bisphenol A type epoxy resin with an epoxy equivalent of 190 g / eq, the curing agent is dicyandiamide, the accelerator is 2-methylimidazole, and the reactive diluent is butyl glycidyl ether.
[0047] S4. Insert the support block and rubber sleeve assembly into the inner hole of the silicon steel sheet of the direct drive motor stator to be potted, so that the end face of the support block fits against the end face of the stator to form a potting assembly. S5. Place the potting assembly in a vacuum environment and inject composite potting compound into the cavity between the inner wall of the stator and the rubber sleeve to obtain the treated part. The absolute pressure of the vacuum environment is ≤50Pa, the surface rise rate of the composite potting compound during injection is 8.5mm / s, and the vacuum is maintained for 2 minutes after injection.
[0048] S6. The processed part is placed in a rotating magnetic field for step curing. The step curing includes a pre-curing stage and a post-curing stage, and a rotating magnetic field is applied in the pre-curing stage. The pre-curing process involves raising the temperature from room temperature to 75°C at a rate of 1.5°C / min and holding it at that temperature for 60 minutes. The post-curing process involves raising the temperature to 120°C at a rate of 1.15°C / min and holding it at that temperature for 2.5 hours after the pre-curing process.
[0049] The rotating magnetic field is applied at the beginning of the pre-curing insulation, with a magnetic field strength of 0.3T and a rotation speed of 90rpm. The rotating magnetic field is turned off when the temperature rises to 102.5℃.
[0050] S7. After the stepped solidified part has cooled naturally, remove the support block rubber sleeve assembly from the stator to complete the demolding.
[0051] The cooling process involves naturally cooling the material inside the furnace to ≤40℃, then removing it and allowing it to stand at room temperature until the surface temperature matches the ambient temperature. The total cooling time is 1.75 hours. The tensile force applied along the axial direction of the support block during demolding is 20N. After demolding, the outer surface of the magnetically responsive silicone sleeve is wiped with a lint-free cloth dampened with anhydrous ethanol.
[0052] Example 2: This example differs from Example 1 above in that: A simplified potting process for a direct-drive motor stator based on a rubber sleeve and a support block includes the following steps: In S1, the processed rubber sleeve is obtained, including the following steps: By weight, 105 parts of methyl vinyl silicone rubber raw rubber, 5 parts of nano iron oxide particles, 20 parts of fumed silica, and 1.5 parts of vulcanizing agent are mixed and molded to obtain a magnetically responsive silicone sleeve. The average particle size of the nano iron oxide particles is 50 nm. The bottom sol was prepared by mixing silica sol and methyltriethoxysilane in a molar ratio of 1:1.3, and the surface fluorosilane was an anhydrous ethanol solution of perfluorodecyltrimethoxysilane with a mass fraction of 2%.
[0053] In S2, eight axial grooves are evenly distributed along the circumference of the outer circular step. The top surface of the polyetheretherketone (PEEK) isolation strip is 0.08 mm lower than the outer circular surface of the support block. The surface of the non-ferromagnetic support block is plated with a hard chromium layer with a thickness of 15 μm.
[0054] In S3, the preparation of the composite potting compound includes the following steps: By weight, 105 parts of epoxy resin, 1.8 parts of first expanded microspheres, 1.8 parts of second expanded microspheres, 12 parts of curing agent, 0.8 parts of accelerator and 7 parts of reactive diluent are mixed, stirred evenly and degassed to obtain composite potting compound.
[0055] The first expanding microsphere has an expansion initiation temperature of 78℃, an average particle size of 30μm, and a maximum expansion ratio of 5 times. The second expanding microsphere has an expansion initiation temperature of 98℃, an average particle size of 35μm, and a maximum expansion ratio of 4 times.
[0056] The epoxy resin is a bisphenol A type epoxy resin with an epoxy equivalent of 200 g / eq.
[0057] In S5, the absolute pressure of the vacuum environment is ≤50Pa, the surface rise rate of the composite potting compound is 12mm / s during injection, and the vacuum is maintained for 3 minutes after injection.
[0058] In S6, pre-curing is performed by raising the temperature from room temperature to 77°C at a rate of 2°C / min and holding it at that temperature for 70 minutes. Post-curing is performed by raising the temperature to 125°C at a rate of 1.5°C / min and holding it at that temperature for 3 hours after pre-curing.
[0059] The rotating magnetic field is applied at the beginning of the pre-curing insulation, with a magnetic field strength of 0.4T and a rotation speed of 120rpm. The rotating magnetic field is turned off when the temperature rises to 105℃.
[0060] In S7, the total cooling time is 3 hours, and the tensile force applied along the support block axis during demolding is 30N.
[0061] Example 3: This example differs from Example 1 above in that: A simplified potting process for a direct-drive motor stator based on a rubber sleeve and a support block includes the following steps: In S1, the processed rubber sleeve is obtained, including the following steps: By weight, 95 parts of methyl vinyl silicone rubber raw rubber, 3 parts of nano iron oxide particles, 10 parts of fumed silica and 1 part of vulcanizing agent are mixed and molded to obtain magnetically responsive silicone sleeves. The average particle size of the nano iron oxide particles is 30 nm. The bottom sol was prepared by mixing silica sol and methyltriethoxysilane in a molar ratio of 1:1.1, and the surface fluorosilane was an anhydrous ethanol solution of perfluorodecyltrimethoxysilane with a mass fraction of 1%.
[0062] In S2, six axial grooves are evenly distributed along the circumference of the outer circular step. The top surface of the polyetheretherketone (PEEK) isolation strip is 0.03 mm lower than the outer circular surface of the support block. The surface of the non-ferromagnetic support block is plated with a hard chromium layer with a thickness of 10 μm.
[0063] In S3, the preparation of the composite potting compound includes the following steps: By weight, 95 parts of epoxy resin, 1.2 parts of first expanded microspheres, 1.2 parts of second expanded microspheres, 8 parts of curing agent, 0.3 parts of accelerator and 3 parts of reactive diluent are mixed, stirred evenly and degassed to obtain composite potting compound.
[0064] The first expanding microsphere has an expansion initiation temperature of 72℃, an average particle size of 20μm, and a maximum expansion ratio of 3 times. The second expanding microsphere has an expansion initiation temperature of 92℃, an average particle size of 25μm, and a maximum expansion ratio of 3 times.
[0065] The epoxy resin is a bisphenol A type epoxy resin with an epoxy equivalent of 180 g / eq.
[0066] In S5, the absolute pressure of the vacuum environment is ≤50Pa, the surface rise rate of the composite potting compound is 5mm / s during injection, and the vacuum is maintained for 1 minute after injection.
[0067] In S6, pre-curing is performed by raising the temperature from room temperature to 73°C at a rate of 1°C / min and holding for 50 minutes. Post-curing is performed by raising the temperature to 115°C at a rate of 0.8°C / min and holding for 2 hours after pre-curing.
[0068] The rotating magnetic field is applied at the beginning of the pre-curing insulation process, with a magnetic field strength of 0.2T and a rotation speed of 60rpm. The rotating magnetic field is turned off when the temperature rises to 100℃.
[0069] In S7, the total cooling time is 1.5 hours, and the tensile force applied along the support block axis during demolding is 10N.
[0070] Comparative Example 1: This comparative example differs from Example 1 above in that: In S1, after preparing the magnetically responsive silicone sleeve, no anti-sticking treatment is applied to the outer surface of the sleeve. That is, the plasma activation treatment, spraying of the bottom layer sol and spraying of the top layer fluorosilane are omitted. The magnetically responsive silicone sleeve after molding is directly used in subsequent steps, and the rest is the same as in Example 1.
[0071] Comparative Example 2: This comparative example differs from Example 1 above in that: In S3, when preparing the composite potting compound, the first and second expanded microspheres are not added, and the rest is the same as in Example 1.
[0072] Comparative Example 3: This comparative example differs from Example 1 above in that: In S3, when preparing the composite potting compound, only 3 parts of the first expanded microspheres are added, and the second expanded microspheres are not added. The rest is the same as in Example 1.
[0073] Comparative Example 4: This comparative example differs from Example 1 above in that: In S6, no rotating magnetic field is applied during the step curing process, meaning that both the pre-curing and post-curing stages are carried out under magnetic field-free conditions, and the rest is the same as in Example 1.
[0074] Comparative Example 5: This comparative example differs from Example 1 above in that: In S2, the support block is made of 45 steel, and there are no axial grooves on the outer circular step. PEEK isolation strips are not embedded, and the surface is plated with a hard chrome layer with a thickness of 12.5μm. The rest is the same as in Example 1.
[0075] Performance testing: Curing volume shrinkage rate: According to GB / T 2567-2021 "Test Methods for Performance of Resin Castings", the volume change rate of the potting compound before and after curing was determined by density method. The potting compound was injected into a special mold and cured according to the curing procedures of each example and comparative example. The density before and after curing was measured and the volume shrinkage rate was calculated. Winding radial displacement: Using a coordinate measuring machine, measure the radial coordinates of at least 8 equally divided points on the same circumference of the stator inner hole before and after potting, and calculate the average value of the radial displacement of each measuring point; Demolding force: Use a push-pull force gauge to pull the end of the support block at a constant speed along the axial direction of the support block, and record the maximum pulling force when the support block rubber sleeve assembly and the stator begin to slide relative to each other; Stator internal bubble rate: The stator after potting was inspected using an X-ray non-destructive testing instrument. At least three X-ray images of different axial sections were taken. The proportion of bubble area in the winding region was statistically analyzed using image analysis software, and the average value was taken. Number of times the rubber sleeve is reused: The same support block rubber sleeve assembly is repeatedly potted according to the process of the example or comparative example until the demolding force exceeds 50N or obvious damage such as cracks or coating peeling area >10% appears on the surface of the rubber sleeve. Record the number of qualified uses. Three samples are tested in each group and the average value is taken. The test results are shown in Table 1.
[0076] Table 1: Potting performance test results of each embodiment and comparative example As can be seen from Example 1 and Comparative Example 1 and Table 1, the anti-stick coating treatment can achieve low-resistance demolding. This treatment reduces the interfacial adhesion between the outer surface of the sleeve and the potting compound by forming a fluorosilane modification layer on the surface of the sleeve, thereby ensuring that the support block sleeve assembly can be smoothly pulled out after curing, and significantly extending the reuse cycle of the sleeve.
[0077] As can be seen from Example 1 and Comparative Example 2, and Table 1, the dual-microsphere system composed of the first and second expanded microspheres can suppress the curing shrinkage of the potting compound. This dual-microsphere system can trigger expansion in stages during the pre-curing and post-curing stages, compensating for the volume shrinkage at different stages of resin curing from the source, thereby effectively controlling the radial displacement of the stator winding.
[0078] As can be seen from Example 1 and Comparative Example 3, and Table 1, the combination of two microspheres with different expansion initiation temperatures is superior to the compensation effect of a single microsphere. A single microsphere can only cover the shrinkage requirements of a portion of the curing temperature range, while the sequential combination of the two microspheres can achieve step-by-step compensation for shrinkage throughout the curing process, ensuring the dimensional stability of the potting compound after curing.
[0079] As can be seen from Example 1 and Comparative Example 4, and Table 1, applying a rotating magnetic field during the pre-curing stage can reduce the demolding force. This rotating magnetic field can induce the nano-iron oxide particles in the sleeve to oriented, causing the sleeve molecular chains to oriented, so that the sleeve has the ability to actively yield stress during the curing process, thereby reducing the accumulation of interfacial stress, facilitating demolding operations and improving the long-term stability of the sleeve.
[0080] As can be seen from Example 1 and Comparative Example 5, and Table 1, the use of non-ferromagnetic support blocks combined with axial groove structures is beneficial to maintaining a uniform distribution of the magnetic field. Ferromagnetic materials will be magnetized in the magnetic field, thereby interfering with the direction of the magnetic lines of force and affecting the orientation effect of the magnetic particles inside the sleeve. The non-ferromagnetic support blocks combined with the groove structure can ensure the effective effect of the rotating magnetic field on the sleeve, thereby giving full play to the stress relief function of the sleeve.
[0081] As can be seen from Examples 1 to 3 and Comparative Examples 1 to 5, and Table 1, the synergistic combination of anti-stick coating treatment, dual-trigger temperature expansion microsphere system, rotating magnetic field-assisted curing, and non-ferromagnetic support structure can reduce demolding resistance while controlling the volume shrinkage of the potting compound during curing, and ensure that the sleeve has a long reusable cycle. Overall, the potting process is simplified and stabilized.
[0082] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.
Claims
1. A simplified potting process for a direct-drive motor stator based on a rubber sleeve and a support block, characterized in that, Includes the following steps: S1. Prepare a magnetically responsive silicone sleeve and perform an anti-sticking treatment on the surface of the magnetically responsive silicone sleeve to obtain a treated sleeve. The magnetically responsive silicone sleeve contains nano-iron oxide particles. S2. The processed rubber sleeve is interference-fitted onto the outer circular step of the non-ferromagnetic support block to form a support block rubber sleeve assembly. S3. Prepare a composite potting compound, wherein the composite potting compound comprises epoxy resin, a first expanded microsphere, and a second expanded microsphere; S4. Insert the support block and rubber sleeve assembly into the inner hole of the silicon steel sheet of the direct drive motor stator to be potted, so that the end face of the support block fits against the end face of the stator to form a potting assembly. S5. Place the potting assembly in a vacuum environment and inject the composite potting compound into the cavity between the inner wall of the stator and the rubber sleeve to obtain the treated part. S6. The processed part is placed in a rotating magnetic field for step curing, the step curing includes a pre-curing stage and a post-curing stage, and a rotating magnetic field is applied in the pre-curing stage. S7. After the stepped solidified part has cooled naturally, remove the support block rubber sleeve assembly from the stator to complete the demolding.
2. The simplified potting process for a direct-drive motor stator based on a rubber sleeve and a support block according to claim 1, characterized in that: In step S1, obtaining the processed rubber sleeve includes the following steps: By weight, 95-105 parts of methyl vinyl silicone rubber raw rubber, 3-5 parts of nano iron oxide particles, 10-20 parts of fumed silica, and 1-1.5 parts of vulcanizing agent are mixed and molded to obtain a magnetically responsive silicone sleeve. The average particle size of the nano iron oxide particles is 30-50 nm. The outer surface of the magnetically responsive silicone sleeve is subjected to plasma activation treatment, spraying of a base layer sol and spraying of a surface layer of fluorosilane in sequence to form an anti-stick coating, thus obtaining the treated sleeve. The base layer sol is prepared by mixing silica sol and methyltriethoxysilane in a molar ratio of 1:1.1 to 1.3, and the surface layer of fluorosilane is an anhydrous ethanol solution of perfluorodecyltrimethoxysilane with a mass fraction of 1 to 2%.
3. The simplified potting process for a direct-drive motor stator based on a rubber sleeve and a support block according to claim 1, characterized in that: In step S2, the non-ferromagnetic support block is made of 304 austenitic stainless steel or beryllium copper alloy. The outer circular step is uniformly provided with 6 to 8 axial grooves along the circumference. Polyether ether ketone (PEEK) isolation strips are embedded in the grooves. The top surface of the PEEK isolation strips is 0.03 to 0.08 mm lower than the outer circular surface of the support block. The surface of the non-ferromagnetic support block is plated with a hard chromium layer with a thickness of 10 to 15 μm.
4. The simplified potting process for a direct-drive motor stator based on a rubber sleeve and a support block according to claim 1, characterized in that: In step S3, the preparation of the composite potting compound includes the following steps: By weight, 95-105 parts of epoxy resin, 1.2-1.8 parts of first expanded microspheres, 1.2-1.8 parts of second expanded microspheres, 8-12 parts of curing agent, 0.3-0.8 parts of accelerator and 3-7 parts of reactive diluent are mixed, stirred evenly and degassed to obtain composite potting compound.
5. A simplified potting process for a direct-drive motor stator based on a rubber sleeve and a support block according to claim 4, characterized in that: The first expandable microsphere has an expansion initiation temperature of 72-78℃, an average particle size of 20-30μm, and a maximum expansion ratio of 3-5 times. The second expandable microsphere has an expansion initiation temperature of 92-98℃, an average particle size of 25-35μm, and a maximum expansion ratio of 3-4 times.
6. The simplified potting process for a direct-drive motor stator based on a rubber sleeve and a support block according to claim 4, characterized in that: The epoxy resin is a bisphenol A type epoxy resin with an epoxy equivalent of 180-200 g / eq, the curing agent is dicyandiamide, the accelerator is 2-methylimidazole, and the reactive diluent is butyl glycidyl ether.
7. A simplified potting process for a direct-drive motor stator based on a rubber sleeve and a support block according to claim 1, characterized in that: In step S5, the absolute pressure of the vacuum environment is ≤50Pa, the rising speed of the composite potting compound liquid surface during injection is 5-12mm / s, and the vacuum is maintained for 1-3 minutes after injection.
8. A simplified potting process for a direct-drive motor stator based on a rubber sleeve and a support block according to claim 1, characterized in that: In step S6, the pre-curing is carried out by raising the temperature from room temperature to 73-77°C at a heating rate of 1-2°C / min and holding it at that temperature for 50-70 minutes. The post-curing is carried out by raising the temperature to 115-125°C at a heating rate of 0.8-1.5°C / min and holding it at that temperature for 2-3 hours after the pre-curing is completed.
9. A simplified potting process for a direct-drive motor stator based on a rubber sleeve and a support block according to claim 1, characterized in that: In step S6, the rotating magnetic field is applied at the beginning of the pre-curing and heat preservation process, with a magnetic field strength of 0.2 to 0.4 T and a rotation speed of 60 to 120 rpm. The rotating magnetic field is turned off when the temperature rises to 100 to 105°C.
10. A simplified potting process for a direct-drive motor stator based on a rubber sleeve and a support block according to claim 1, characterized in that: In step S7, the cooling is to take it out after natural cooling in the furnace to ≤40℃, and then let it stand at room temperature until the surface temperature is the same as the ambient temperature. The total cooling time is 1.5 to 3 hours. The tensile force applied along the axial direction of the support block during demolding is 10 to 30N. After demolding, the outer surface of the magnetic response silicone sleeve is wiped with a lint-free cloth dipped in anhydrous ethanol.